An exploration on in-situ synthesis of europium doped g-C3N4 for photocatalytic water splitting. (February 2019) - Tang, Junying; Zhou, Weiguo; Guo, Ruitang; Huang, Chunying; Pan, Weiguo; Liu, Pengcheng
Abstract: Eu doped g-C3 N4 composites with different contents (2%, 4%, 5%) were successfully synthesized by a facile in-situ method. Comprehensive characterizations including X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscope (TEM), N2 adsorption-desorption and UV–vis diffuse reflectance revealed that the introduction of Eu affected the surface, structural and optical properties of the photocatalyts. The photocatalytic activity of Eu/g-C3 N4 catalysts was tested for water splitting under the visible light irradiation, and it exhibited superior performance. A maximum H2 yields of 2425.7 umol ▪ g-cat had been obtained on 4% Eu/g-C3 N4 catalyst, which was about 4.0 times as high as the pure g-C3 N4 . The excellent photocatalytic performance may be ascribed to the high specific surface area and enhanced visible-light absorption. The work provides meaningful guidelines for improving photocatalytic activity by rare earth elements modifying.